Overall equipment efficiency: estudo de caso a partir da previsão aplicada ao processo de gestão e falhas - Pereira, Marcelo Medeiros (2018)
To develop or differentiate competitively, companies need to identify production opportunities, to develop new conceptions for management strategies, using information from all hierarchical levels, to fully understand their processes. This is possible from a business enterprise, with the purpose of boosting the investments by the organization. The implementation of a law continued in the process of production, together with the use of tools that aim to aid decision making, by providing information the possibility of production. Thus, this study aimed to analyze the behavior of the records from production stops, in an intermittent series with presence of volatility, to issue an opinion about the beverage industry, through the use of econometric models, applied in conjunction with the analysis of overall efficiency. of the equipment, in the period from 2012 to 2016. The data were sent to the intermittent time, adjusted by the Croston method, aiming to fill an intermittent series for the values equal to zero. It was used to predict the AR (1) - ARCH (1) model, being the best fit between the investigated models for the machine shutdown times records, and it can be considered as a reference for industries that there are intermittent series for the fault management. The overall efficiency of the equipment and products of the period were affected by the variability in the production stops in the machine park.